Molluscum contagiosum/Superficial lymphangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Molluscum contagiosum and superficial lymphangioma are two very different disorders. However, their lesions, size and tendency to cluster are similar, so that in some cases, when lymphangioma has appeared recently, some diagnostic doubt may arise.